Dog science unleashed : fun activities to do with your canine companion - Wheeler-Toppen, Jodi; Rakola, Matthew (Washington, DC : National Geographic, 2018)
Learn about science with the most faithful lab partner you'll ever have -- your dog! Discover how your canine companion thinks, moves, drinks, stays warm, gets clean, cools off, and more. Have fun with 22 safe and pup-friendly activities that let you work alongside your dog to discover what makes him tick. Learn to take your dog's pulse and find out how much blood is pumping through his body. Find out if your dog hears things you can't by making a dog whistle. What colors can your dog see? Is he color-blind? Each activity is paired with step-by-step instructions, clear and interesting scientific explanations, and cool photographs shot specifically for this book. Hands-on activities and fun information for budding scientists prompt further learning and offer a behind-the-scenes look at current canine research. When you are finished with the book you'll have a vet-worthy profile of the best canine companion on the planet--yours!
Sniffing out senses -- Fit Fido -- Clever canines -- Pampered pooches.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Age 9-12.
Grade 4 to 6.
Includes bibliographical references (page 77) and index.
Description based on print version record.
Keywords: Dogs -- Juvenile literature; Dogs -- Behavior -- Juvenile literature; Dogs; Dogs -- Behavior; JUVENILE NONFICTION -- Animals -- Dogs; JUVENILE NONFICTION -- Science & Nature -- Zoology; Dogs; Dogs -- Behavior; Electronic books- OSLIS; Juvenile works; Literature; Juvenile works; Literature; Juvenile works; Electronic books